The Effects from Stair Climbing on Postural Control During Sit-to-Stands - Crake, Dylan (Université d'Ottawa / University of Ottawa, 2017)
Rising up from a chair (sit-to-stand; STS) and stair climbing are both activities of daily living (ADLs) done throughout our lives. The ability to complete ADLs is crucial for independent living. The goal of this thesis was to research how two ADLs interact with each other and affect postural control. It was hypothesized that an increased number of flights of stairs climbed would lead to a decline in postural control during/after a STS in older more than younger adults. Fourteen older adults and fourteen young adults were tested by completing three STSs before and after climbing 1, 3 and 5 flights of stairs, chosen at random. Movements of the center of pressure (COP) for each STS were obtained from a force platform. Only an age effect was found for COP velocity (left-right and anterior-posterior directions) during the momentum transfer phase, during stabilization and after stabilization. Therefore, contrary to our hypothesis, stair climbing did not lead to significant changes in COP movements during and following a STS.
Keywords: Sit-to-stands; Stair climbing; Older adults; Postural control